Chemical Consequences of the Mechanical Bond: A Tandem Active Template‐Rearrangement Reaction. (14th February 2019) - Modicom, Florian; Jamieson, Ellen M. G.; Rochette, Elise; Goldup, Stephen M.
Abstract: We report the unexpected discovery of a tandem active template CuAAC‐rearrangement process, in which N2 is extruded on the way to the 1, 2, 3‐triazole product to give instead acrylamide rotaxanes. Mechanistic investigations suggest this process is dictated by the mechanical bond, which stabilizes the Cu I ‐triazolide intermediate of the CuAAC reaction and diverts it down the rearrangement pathway; when no mechanical bond is formed, the CuAAC product is isolated. Abstract : Bei der unerwarteten Entdeckung einer Tandem‐AT‐CuAAC‐Umlagerung (AT=aktives Templat) wird auf dem Weg zum 1, 2, 3‐Triazolprodukt N2 freigesetzt und so stattdessen ein Acrylamid‐Rotaxan gebildet. Mechanistischen Studien zufolge wird dieser Prozess durch die mechanische Bindung bestimmt, welche die bevorzugte Protonierung einer OH‐Abgangsgruppe anstelle der reaktiven Cu‐C‐Bindung ermöglicht und so die Umlagerung auslöst.